New Perspectives on Jacob von Stählin: Towards an Intellectual Biography*. (2nd January 2018) - Larocca, Giuseppina
ABSTRACT: The article is devoted to Jacob von Stählin, an important figure of the eighteenth-century Russian Culture. The contribution is an attempt to reconstruct his intellectual biography based on new archival researches. The role of Stählin from the 1735 to his death is provided, paying particular attention to his work as a poet and his contribution to the Academy of Sciences and the artistic activities.